Construcción De Un Prototipo De Automatización Para El Proceso De Pegado De Boquillas Del Eyector De Saliva Fabricado En Tecnomecanizados Dalton Sas. (2024)
The company TECNOMECANIZADOS DALTON S.A.S., a manufacturer of medical devices, markets a product used in the dental industry called Saliva Ejector. This product undergoes a process of manufacturing, assembly, packaging, and final delivery. This project is based on the construction of a prototype that automates the nozzle gluing process, which reduces labor costs and time spent, factors that increase the company’s productivity and competitiveness both nationally and internationally. To achieve this objective, a quantitative analysis of the current performance of the gluing process was carried out, evaluating the available conditions for the implementation of the automated process, such as the space allocated for it, project costs, and the selection of possible materials that are resistant, non-abrasive, or non-contaminating to the raw material. Finally, an automatic gluing prototype was designed, concluding that it improves the process performance by 90 %, and enhances the company’s response capacity to the current market demand.